Failure of oral thiomalate to act as an alternative to intramuscular gold in rheumatoid arthritis. Issue 3 (March 1988) - Rudge, S R; Perrett, D; Kelly, M
Abstract : Ten patients with active rheumatoid arthritis (RA) were entered into a pilot study to evaluate the effectiveness of thiomalic acid as a disease modifying agent and to assess its toxicity. Oral thiomalic acid (100 mg) was given daily for up to six months. Changes in disease activity were recorded monthly and all side effects noted. No patient recorded any improvement in subjective well being, pain score, or duration of early morning stiffness. No significant change occurred in articular index or haemoglobin (Hb); the erythrocyte sedimentation rate (ESR) showed a tendency to increase. Only three patients completed six months' treatment; six withdrew because of toxic reactions (three with rashes and three with severe gastrointestinal upset) and one because of lack of effect. Thiomalic acid alone appears to have no significant antirheumatic activity and is associated with an unacceptably high incidence of adverse reactions.